The relationship between career development, compensation, job security, work environment and employee loyalty / Muhammad Faizal Samat ... [et al.] - Samat, Muhammad Faizal; Hamid, Muhammad Najmuddin; Awang@Ali, Muhammad Ameer Shafiq; Wan Juahari, Wan Muhammad Iqmal Fazri; Ghazali, Khairul Asraf; Mat Nawi, Farahiyah Akmal (2020)
Malaysia has recorded the second highest involuntary turnover rate at 6% and third highest voluntary rate at 6.5% in South East Asia. Employee loyalty becomes critical towards employer. Thus, the purpose of this study was to examine the relationship between career development, compensation, job security, work environment and employee loyalty. In conducting this study, convenience sampling technique has been employed and respondents have been chosen in the area of Kuala Lumpur. Hypothesis were tested using regression analysis by using Smart-PLS. Based on the result, career development, compensation and job security were found to be significant with employee loyalty. However, work environment was found to be not significant with employee loyalty. It is suggested for future research to explore other variables in order to find the factors contributed in employee loyalty.